Odpowiedzi

2010-04-10T21:50:39+02:00
A) c= (k+1)b + 2k
c=kb+b+2k
c-b=kb+2k
c-b=k(b+2) |:(b+2)
(c-b)/(b+2)=k
k=(c-b)/(b+2)

b) d= k/k-1 |*k-1
d(k-1)=k
dk-d=k
dk-k=d
k(d-1)=d |:(d-1)
k=d/(d-1)

c) e=k-1/k+1 |*k+1
e(k+1)=k-1
ek+e=k-1
ek-k=-1-e
k(e-1)=-1-e |:(e-1)
k=(-1-e)/(e-1)

d) f= k+1/k +a |*(k+a)
f(k+a)=k+1
fk+fa=k+1
fk-k=1-fa
k(f-1)=1-fa |:(f-1)
k=(1-fa)/(f-1)

e) g= 2- 1/k |*k
gk=2-1 |:g
k=1/g

f) h= ka² + k
h=k(a2+1) |:(a2+1)
k=h/(a2+1)

g) i=a/2 + 2/k |*2k
2ki=ak+4
2ki-ak=4
k(2i-a)=4 |:(2i-a)
k=4/(2i-a)
23 5 23
2010-04-10T22:00:39+02:00
A)
c=(k+1)b+2k
c=kb+b+2k
c-b=2k+kb
c-b=k(2+b)
k=(c-b)\(2+b)
b)
d=k\k-1 \*k-1
d(k-1)=k
dk-d=k
dk-k=d
k(d-1)=d
k=d\d-1
c)
e=k-1\k+1 \*k+1
e(k+1)=k-1
ek+e=k-1
ek-k=-1-e
k(e-1)=-1-e
k=(-1-e)\e-1
d)
f=k+1\k+a \*k+a
f(k+a)=k+1
fk+fa=k+1
fk-k=1-fa
k(f-1)=1-fa
k=(1-fa)\(f-1)
e)
g=2-1\k
g-2=-1\k \*k
k(g-2)=-1
k=-1\g-2
f)
h=ka kwadrat+k
h=k(a kwadrat +1)
k=h\a kwadrat+1
g)
i=a\2 +2\k
i-a\2=2\k \*k
k(i-a\2)=2
k=2\(i-a\2)

2 1 2